White paper on the future of plasma science and technology in plastics and textiles. Issue 1 (8th June 2018) - Cvelbar, Uroš; Walsh, James L.; Černák, Mirko; de Vries, Hindrik W.; Reuter, Stephan; Belmonte, Thierry; Corbella, Carles; Miron, Camelia; Hojnik, Nataša; Jurov, Andrea; Puliyalil, Harinarayanan; Gorjanc, Marija; et al.
Abstract : This white paper considers the future of plasma science and technology related to the manufacturing and modifications of plastics and textiles, summarizing existing efforts and the current state‐of‐art for major topics related to plasma processing techniques. It draws on the frontier of plasma technologies in order to see beyond and identify the grand challenges which we face in the following 5–10 years. To progress and move the frontier forward, the paper highlights the major enabling technologies and topics related to the design of surfaces, coatings and materials with non‐equilibrium plasmas. The aim is to progress the field of plastics and textile production using advanced plasma processing as the key enabling technology which is environmentally friendly, cost‐efficient, and offers high‐speed processing. Abstract : This white papers tries to outline the future of plasma science and technology related to plastics and textiles with the current state‐of‐the‐art and grand challenges, which needs to be addressed to move the frontier of this field. Readers will learn where we stand today, and where do we want to go in the future. It is a "navigation chart" for plasma in plastics and textiles for everyone who is interested in the field!